Thermo-Physiological Comfort Property of Military Combat Boot Material for Hot and Cold Climatic Conditions - Weldeyesus Wendowesen Bekele (Advances in Materials Science and Engineering)
Military combat boots require materials that balance thermo-physiological comfort in hot and cold climates. The aim of this research was to analyze the thermo-physiological comfort properties of military combat boot materials in extreme hot and cold conditions to maintain optimal functionality. One-way ANOVA and Tukey’s pairwise comparison statistical tests were conducted, resulting in a p value less than 0.05, indicating statistically significant differences between the materials’ air permeability, water vapor permeability, and thermal resistance. For hot climates, plain nylon canvas four-thread upper and warp-knitted lining fabrics had thermo-physiological indexes of 8.15 and 119.5, respectively. The high airflow and moisture wicking of these materials kept feet cool and dry. For cold climates, chrome-tanned waterproof upper leather and sheepskin lining leather had thermo-physiological indexes of 33.33 and 24.18, respectively. Their waterproofing and insulation maintained warmth and dryness. The thermal properties of the sample uppers were determined to evaluate breathability and insulating ability for hot and cold climatic conditions. The selection of proper materials for military combat boots in different climates is the main approach to reducing foot heat, foot pain, and foot injuries under any condition, providing comfort for wearers, and protecting feet against harsh conditions.